O ensino interdisciplinar entre física e matemática: uma nova estratégia para minimizar o problema da falta dos conhecimentos matemáticos no desenvolvimento do estudo da física - Lima Neto, Willis Sudário de (2011)
This paper describes an application of an interdisciplinary approach between mathematics and physics, in order to compensate for the lack in some basic math concepts in learning physics. This new methodology is to review all of the mathematical content needed for good development and learning in physics, for it was made a material that combines the content being taught in physics with the content required for this study. This methodology and the material was applied to a state school in the municipality of Rio de Janeiro in a class of first year of high school, emphasizing the part of linear expansion of solids, seeking to discover the influence that a good mathematical background may have learning of Physics.